Evaluasi Kepuasan Pengguna Rekam Medis Elektronik dengan Metode EUCS di Rumah Sakit Duta Indah - Siti Nur Azizah Jamil; Muhammad Rezal; Noor Yulia; Muhammad Fuad Iqbal (Antigen : Jurnal Kesehatan Masyarakat dan Ilmu Gizi, 2025)
This study aims to evaluate and identify the obstacles faced and provide recommendations for improvements to the satisfaction of Electronic Medical Records (EMR) users at Duta Indah Hospital using the End User Computing Satisfaction (EUCS) method. At Duta Indah Hospital the EMR system used is Medinfras. EUCS is used to measure user satisfaction with the application system by comparing user expectations with the reality experienced. This evaluation examines seven variables: content, display (format), accuracy, ease of use, timeliness, speed, and flexibility. This research method uses descriptive quantitative with 63 respondents selected as samples. Data were collected through an online questionnaire, processed using Microsoft Excel 2016 software and analyzed using SPSS Version 25 software with a Likert scale to measure the level of satisfaction. The results showed that the majority of users felt "quite satisfied" with all variables, namely: content (57%), display (57%), timeliness (59%), speed (58%), flexibility (56%), accuracy (54%) and ease of use (54%). In conclusion, the RME system is considered quite adequate in supporting user performance, with accurate information, easy-to-understand displays, and efficiency in time and flexibility. The suggestion for the hospital is to conduct an evaluation, improve the appearance of the system menu so that users can access the system more easily and improve regular system maintenance.